A blaze of sun - Forrest, Bella (Forrest, Bella. Shade of vampire, 2013)
Ever since his brief encounter with Emilia at The Shade, Derek's thoughts and dreams have been haunted with images of the mysterious, beautiful brunette. Plagued with guilt, he struggles to understand why he is so drawn to this dark stranger from his past. When Emilia suddenly appears again on the island, Derek is both terrified and intrigued. But this time, he is determined to involve Sofia and discover who this woman is. If only Derek and Sofia knew, Emilia is a mystery that should be left undiscovered...